Can optic nerve sheath meningioma affect the post-operative course after trabeculectomy? – case report - Post, Michał; Durajczyk, Magdalena; Lubiński, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
The authors report a case of a 37-year-old man treated due to concomitant open-angle glaucoma and chronic optic disc oedema in his left eye. During 4-year observation the patient underwent routine glaucoma treatment and periocular triamcinolone injections, with periodical resolution of symptoms (visual snow) and improvement in the eye electrophysiological performance. During diagnostic proceeding, including routine ophthalmological examinations and extensive imaging and electrophysiological examinations (CT, MRI, angioMRI), left-sided optic nerve sheath meningioma was diagnosed. Due to intolerance of topical medicines and fluctuation of intraocular pressure, trabeculectomy with mitomycin was performed in the patient, complicated with chronic choroidal effusion and hypotony maculopathy. In the discussion, the authors analyse the potentially adverse effect of optic nerve sheath meningioma on the persistent nature of post-operative complications. The trabeculectomy procedure in this group of patients seems to be increased-risk surgery and is not recommended. Therefore in patients with optic nerve sheath meningioma procedures associated with lower risk of post-operative hypotony (minimally invasive glaucoma surgery (MIGS), valves) should be considered.